Morphological and genetic diversity of Jatropha curcas L. in Malaysia. - Shabanimofrad, Mahmoodreza (2011)
Considering vast semi wild distribution of J. curcas species, genetic diversity should be existed in different parts of Peninsular Malaysia. Unfortunately, there is no information on the genetic diversity of this species in this country, while the knowledge of genetic variability of J. curcas is completely necessary for introducing its breeding programs. For this purpose, a study of different J. curcas accessions in Malaysia is required to identify highly potential elite accessions that are capable of high sustainable yields in different agro-climatic zones. Fifty nine J. curcas accessions were collected from Selangor, Kelantan and Terengganu states were evaluated in-situ and ex-situ and also by molecular (RAPD)markers. The objectives were to determine the genetic variation and diversity of J.curcas accessions in three states of Malaysia, to evaluate the performance of different accessions of J. curcas, to assess variability at the molecular level among the accessions and to identify superior J. curcas accessions to develop improved populations. In-situ evaluation of 59 J. curcas based on Zangemeister’s method, Accessions B-05-06, B-02-04, B-05-09, T-01-09, T-01-04, T-01-10, D-01-10, D-01-08 and D-01-06 were distinguished with high oil content, collar diameter, number of fruits per cluster and leaf area. Out of the 59 collected accessions, 48 accessions were survived in nursery and planted in field for evaluation. Results of genetic diversity analysis using 14 morphological characters indicated that the presence of genetic variability among the J. curcas accessions. Broad sense heritability of all the traits were high with values exceeded 63%. Molecular analysis using RAPD markers revealed that the majority of accessions from Selangor state were clustered separately from accessions of other states. This indicated that the genetic divergence of the Selangor accessions compared to all accessions from Kelantan and Terengganu. Two accessions collected from Kelantan and Selangor states, D-01-09 and B-03-02 respectively had relatively higher average total yield, 100-seed weight, oil content and growth characteristics compared to all other accessions. Finally, this study provides important insight in the accessions of J. curcas and this finding could be used as background information for breeding and improvement program of this species in Malaysia